Techno-economic assessment of PV system in socialized residential low-rise buildings in Metro Manila - Bien, Michael Bryan M.; Tamayao, Mili-Ann M. (Quezon City College of Engineering, University of the Philippines Diliman, 2019)
Residents of socialized housing in Metro Manila spend about Php 800/month on electricity which is around 7% of the total household expenses. Rooftop solar photovoltaic (PV) systems are seen to be a way to reduce electricity costs as well as environmental impacts. However, results from previous economic viability analyses have been inconclusive due to varying tariff structures, resource availability, system installed costs, discount rates, etc. for different countries. This study developed a framework for the investigation of the economic viability of rooftop solar PV systems for socialized residential low-rise buildings (LRB) in Metro Manila. One building in Paradise Heights was used to represent the socialized LRBs in the study. Several system designs were analyzed using HOMER Pro. These configurations included grid-connected PV systems under the net-metering scheme (with or without battery) and PV systems with varying area of coverage and roof orientation. Mono-crystalline and poly-crystalline PV modules with 270W and 315/320W capacities were used in the analysis. Results show that for the building used in this study, 320W poly-crystalline PV module system (with battery) configured to have a total capacity of 61.44 kW provided the least net present cost (NPC) of around Php 12.39M. The corresponding levelized cost energy (LCOE) for this system is at Php 5.97/kWh. These numbers are lower than the costs related to the status quo (i.e., grid connection), which has NPC of Php 14.88M ans=d LCOE of Php 9.96/kWh. The annual energy generation for the said system is at 73.45MWh. Under the optimal scenario mentioned above, households are expected to save around PhP 300/month cutting electricity bills by over 30%. Sensitivity analysis indicate that at some conditions, optimal system shifted to the 320W poly-crystalline modle without battery. For the system with battery, improvement on NPC and LCOE was less than 1% only while the increase in capital was more than 11%. Given this, the PV system without battery is preferred. This study shows that rooftop solar PV's for socialized LRBs are economically viable with PV systems with maximized roof area configuration, with the optimal scenario using the 320W poly-crystalline capacity of 61.44W.
Thesis (Master of Science in Energy Engineering)--University of the Philippines Diliman
Keywords: Bioengineering; Energy conservation; Techno-economic assessment